Postnatal mental health, breastfeeding beliefs, and breastfeeding practices in rural China - Qi Jiang; Evelyn Zhang; Nourya Cohen; Mika Ohtori; Sabrina Zhu; Yian Guo; Hannah Faith Johnstone; Sarah-Eve Dill; Huan Zhou; Scott D. Rozelle (BMC, 2022)
Abstract Background The importance of breastfeeding in low- and middle- income countries is well recognized, yet the importance of postnatal mental health on breastfeeding practices and beliefs in these settings has been understudied. This study investigates the associations between maternal mental health problems, breastfeeding beliefs and breastfeeding practices in rural China. Methods Cross-sectional data were collected in November and December 2019 from 742 mothers of infants under 6 months old in rural Sichuan Province, China. Maternal mental health (depression, anxiety, and stress symptoms) was assessed using the Depression, Anxiety, and Stress Scale (short form). Breastfeeding beliefs were assessed using the Iowa Infant Feeding Attitude Scale and Breastfeeding Self-Efficacy Scale (short form). Breastfeeding practices were assessed through a 24-h dietary recall questionnaire. Ordinary least squares regression, multiple logistic regression and heterogeneous effects analyses were used to identify associations between symptoms of mental health problems and breastfeeding outcomes. Results The average age of sample infants was 2.7 months. Among mothers, 13% showed symptoms of depression, 16% anxiety, and 9% stress. The prevalence of exclusive breastfeeding in the previous 24 h was 38.0%. Depression symptoms were significantly associated with breastfeeding attitude (𝛽= − 1.11, 95% CI: − 2.07, − 0.14) and breastfeeding self-efficacy (𝛽= − 3.19, 95% CI: − 4.93, − 1.45). Anxiety and stress symptoms were significantly associated with breastfeeding self-efficacy (𝛽= − 1.81, 95% CI: − 3.43, − 0.18 and 𝛽 = − 2.88, 95% CI: − 4.98, − 0.78, respectively). There were no significant associations between symptoms of mental health problems and exclusive breastfeeding. The heterogeneous effects analyses revealed that less educated mothers with symptoms of stress had lower odds of exclusive breastfeeding than educated mothers without symptoms of stress (OR: 0.53, 95% CI: 0.25,1.10). Mothers of younger infants had higher odds of exclusive breastfeeding than the mother of older infants, regardless of depression, anxiety, or stress symptoms. Conclusion Symptoms of maternal mental health problems are significantly associated with breastfeeding attitude and self-efficacy; however, these symptoms are not associated with breastfeeding practices. Maternal educational level and infant age may play a role in mothers' breastfeeding practices. To improve breastfeeding practices, interventions should employ a multi-dimensional approach that focuses on improving maternal mental well-being and considers demographic characteristics.